Women’s experience of childbirth care in health facilities: a qualitative assessment of respectful maternity care in Afghanistan - Partamin Manalai; Nasratullah Ansari; Hannah Tappis; Young Mi Kim; Jelle Stekelenburg; Jos van Roosmalen; Sheena Currie (BMC Pregnancy and Childbirth, 2024)
Abstract Background Respectful maternity care (RMC) remains a key challenge in Afghanistan, despite progress on improving maternal and newborn health during 2001—2021. A qualitative study was conducted in 2018 to provide evidence on the situation of RMC in health facilities in Afghanistan. The results are useful to inform strategies to provide RMC in Afghanistan in spite of the humanitarian crisis due to Taliban’s takeover in 2021. Methods Focus group discussions were conducted with women (4 groups, 43 women) who had used health facilities for giving birth and with providers (4 groups, 21 providers) who worked in these health facilities. Twenty key informant interviews were conducted with health managers and health policy makers. Motivators for, deterrents from using, awareness about and experiences of maternity care in health facilities were explored. Results Women gave birth in facilities for availability of maternity care and skilled providers, while various verbal and physical forms of mistreatment were identified as deterrents from facility use by women, providers and key informants. Low awareness, lack of resources and excessive workload were identified among the reasons for violation of RMC. Conclusion Violation of RMC is unacceptable. Awareness of women and providers about the rights of women to respectful maternity care, training of providers on the subject, monitoring of care to prevent mistreatment, and conditioning any future technical and financial assistance to commitments to RMC is recommended.